Comerciantes y tesoros de Indias: préstamos y ‘libranzas’ tras la requisa de remesas de 1538 - Sergio Sardone (Nuevo mundo - Mundos Nuevos, 2015)
This article aims to explain the policy of requisitioning of the Americans remittances from a point of view of the payments (libranzas) of the treasures expropriated in 1538, in which circumstance the colonial merchants had been affected by the measure. The study allows drawing a map of the main provinces and the Caribbean islands involved in the extinction of these loans and where the professionals of the colonial commerce established their businesses and networks, providing a projection of their geographical and financial negotiations with the New World.